Pre-Exercise Caffeine and Sodium Bicarbonate: Their Effects on Isometric Mid-Thigh Pull Performance in a Crossover, Double-Blind, Placebo-Controlled Study - Celil Kaçoğlu; İzzet Kirkaya; Halil İbrahim Ceylan; Gilmara Gomes de Assis; Paulo Almeida-Neto; Serdar Bayrakdaroğlu; César Chaves Oliveira; Ali Özkan; Pantelis T. Nikolaidis (MDPI AG, 2024)
Caffeine and sodium bicarbonate are extensively researched ergogenic aids known for their potential to enhance exercise performance. The stimulant properties of caffeine on the central nervous system, coupled with the buffering capacity of sodium bicarbonate, have been associated with improved athletic performance. This has led to investigations of their combined effects on strength. The aim of the present study is to investigate the effect of isolated and combined caffeine and sodium bicarbonate consumption on strength using the isometric mid-thigh pull test (IMTP). Nineteen male college students (age 23.6 ± 1.6 years) participated in this crossover, double-blind, placebo-controlled study. They were exposed to the following conditions: control (no supplement), placebo (20 g maltodextrin), caffeine (6 mg/kg), sodium bicarbonate (0.3 g/kg), and a combination of caffeine and sodium bicarbonate. Supplements and placebo were diluted in water and consumed 60 min prior to the IMTP tests. Two 5 s IMTP trials were performed at 40-60% and 60-80% of One Repetition of Maximum (1RM) with a 60 s rest between. Consumption of caffeine or Caf + NaHCO3 did not significantly change peak IMTP strength values at any intensity (p = 0.110). The peak IMTP values did not show significant differences between conditions or from control condition values (1091 ± 100 N) to Caf (1224 ± 92 N), NaHCO3 (1222 ± 74 N), and Caf ± NaHCO3 (1152 ± 109 N). However, the test of the results of the ANOVA analysis of repeated measures of effect within the caffeine condition was significant for the increase in IMTP relative strength compared to control (p < 0.05). Thus, the IMTP force values increased significantly from control to Caf (p = 0.016) and from Pla to Caf (p = 0.008), but not for other comparisons (p > 0.05). In summary, caffeine supplementation alone, taken 60 min before exercise, positively affects submaximal strength performance. In contrast, sodium bicarbonate, whether taken alone or in combination with caffeine, does not enhance submaximal strength in the IMTP tests.